Hitler's last witness : the memoir of Hitler's bodyguard - Misch, Rochus; Moorhouse, Roger (South Yorkshire, England : Frontline Books, 2014)
After being seriously wounded in the 1939 Polish campaign, Rochus Misch was invited to join Hitler''s SS-bodyguard. There he served until the war''s end as Hitler''s bodyguard, courier, orderly and finally as Chief of Communications. On the Berghof terrace he watched Eva Braun organize parties; observed Heinrich Himmler and Albert Speer; and monitored telephone conversations from Berlin to the East Prussian FHQ on 20 July 1944 after the attempt on Hitler''s life. Towards the end Misch was drawn into the Führerbunker with the last of the ''faithful''. As defeat approached, he remained in charge.
Hitler''s Last Day: 30 April 1945Negotiations and the Goebbels Children: 1 May 1945; Break-out and Capture; My Nine Years in Soviet Captivity; My Homecoming and New Beginnings; Short Biographies; Index.
Includes index.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Misch, Rochus, -- 1917-2013.; Hitler, Adolf, -- 1889-1945.; Allgemeine-SS.; Hitler, Adolf, -- 1889-1945; Misch, Rochus, -- 1917-2013; Allgemeine-SS; World War, 1939-1945 -- Germany -- Berlin -- Personal narratives, German; Bodyguards -- Germany -- Anecdotes; Gardes du corps -- Allemagne -- Anecdotes; HISTORY -- Europe -- Western; Bodyguards; Germany; Germany -- Berlin; 1939-1945; Personal narratives; Anecdotes; Personal narratives -- German; Personal narratives; Récits personnels